ANALISIS PENDAPATAN ASLI DAERAH DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DALAM RANGKA OTONOMI DAERAH : PENDEKATAN ERROR CORRECTION MODEL - Oktavina, Dewi (Jurnal Ekonomi Pembangunan, 2012)
In most its management region autonomy therefore needful a policy in point of local government to increase ability in dig up its own finance potency one of its stemmed one of Propertied Original region (PAD), kerena is PAD'S Proportion to full scale region acceptance makes a abode to constitute financial independence degree indication a local government.Â  To the effect that wants to be reached deep observational it is menganalisis factor that regards PAD. That factor cover: population local government expenditure and PDRB. Observed data in this research is datu runtut periodic time 1994 2008. Estimation model that utilized by Error Correction's Approaching Model.Â